Uma análise de elementos matemáticos presentes na gravura Melancolia I de Albrecht Dürer: poliedro, esfera e quadrado mágico - Paulo, Luís Guilherme Oliveira (Universidade Federal de São Carlos, 2021)
This monograph addresses as its main theme Albrecht Dürer's Melancholia I, an engraving that is full of philosophical and mathematical meanings. With a didactic and mathematical approach, we aim to contextualize the author's life and the work, in addition to discussing some mathematical elements present in the work, dealing with the history, definitions, theorems and some of the main results about the mentioned elements. Finally, we conclude with the work mentioning the importance of mathematics in art and how its history is rich even in times when humanity did not have so much access to technology.
An analysis of mathematical elements present in the engraving Melancholia I by Albrecht Dürer: polyhedron, sphere and magic square
Keywords: Albrecht Dürer; Melancolia I; Poliedro; Esfera; Quadrado mágico; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA